Abnormalities of placental development and function are associated with the different fetal growth patterns of hypoplastic left heart syndrome and transposition of the great arteries. (November 2020) - Courtney, Jennifer; Troja, Weston; Owens, Kathryn J.; Brockway, Heather M.; Hinton, Andrea C.; Hinton, Robert B.; Cnota, James F.; Jones, Helen N.
Abstract: Background: Birthweight is a critical predictor of congenital heart disease (CHD) surgical outcomes. Hypoplastic left heart syndrome (HLHS) is cyanotic CHD with known fetal growth restriction and placental abnormalities. Transposition of the great arteries (TGA) is cyanotic CHD with normal fetal growth. Comparison of the placenta in these diagnoses may provide insights on the fetal growth abnormality of CHD. Methods: Clinical data and placental histology from placentas associated with Transposition of the Great Arteries (TGA) were analyzed for gross pathology, morphology, maturity and vascularity and compared to both control and previously analyzed HLHS placentas [1]. RNA was isolated from HLHS, TGA and control placentas and sequenced by Illumina HiSeq.Transcriptome analysis was performed using AltAnalyze. Immunohistochemistry was utilized to assess placental nutrient transporter expression in all three groups. Results: Placental weight was reduced in TGA cases, and demonstrated reduced villous vasculature, immature terminal villi in the parenchyma compared to controls and reflected our previous data from HLHS placentas. However, birth weight was not reduced in TGA cases compared to controls in contrast to the HLHS cohort and birthweight:placental weight ratio was significantly increased in TGA cases but not HLHS compared to control. Transcriptomic and histologic analysis demonstrates reduced cell activity and nutrient transport capability in HLHS but not TGA placentas which appear to increase/maintain these mechanisms. Conclusions: Despite common vascular disturbances in placentas from HLHAs and TGA, these do not account for the disparities in birthweights frequently seen between these CHD subtypes, in contrast our transcriptomic and histologic analyses reveal differentially regulated mechanisms between the subtypes that may explain these disparities. Highlights: Common vascular and structural disturbances are seen in HLHS and TGA placentas. Placental efficiency is significantly increased in TGA but not HLHS compared to controls. HLHS placenta nutrient transporter expression is altered compared to control and TGA.